Long term follow-up of genetically confirmed patients with familial hypercholesterolemia treated with first and second-generation statins and then with PCSK9 monoclonal antibodies. (September 2020) - Pasta, Andrea; Cremonini, Anna Laura; Formisano, Elena; Fresa, Raffaele; Bertolini, Stefano; Pisciotta, Livia
Abstract: Background and aims: In Italy, the clinical and genetic characteristics of familial hypercholesterolemia (FH) have been extensively assessed in various lipid clinics, although no studies on long-term cardiovascular outcomes in heterozygous patients (He-FH) have been conducted. This study evaluated the incidence of atherosclerotic cardiovascular disease (ASCVD) in He-FH before and after a long-term period of lipid-lowering treatments to ascertain the interference of other risk factors. Methods: A total of 294 genetically characterised He-FH subjects from 1989 to 2019 were retrospectively analysed. General characteristics, lipid profiles, ASCVD prevalence, and ultrasound carotid atherosclerosis assessment were evaluated. Primary end points were ASCVD outcomes and the percentage of patients reaching recommended LDL-C targets. Results: During follow-up, despite a significant improvement in plasma lipid profiles, the ESC/EAS 2016 and 2019 recommended LDL cholesterol (LDL-C) goals were attained in only a few patients treated with anti-PCSK9 monoclonal antibodies added to the maximum tolerated oral therapy with statins plus ezetimibe. Forty-seven subjects had an ASCVD event before starting lipid-lowering therapy (LLT). During follow-up (median 13 years) on LLT, 28 patients had a first ASCVD event and 16 had recurrent ASCVD. In basal conditions and during follow-up, higher LDL-C levels were associated with increased ASCVD risk ( p  < 0.001). Prevention of recurrent ASCVD events was recorded with a long-term reduction of LDL-C below 100 mg/dl with statins plus ezetimibe. Conclusions: PCSK9 inhibition is the only therapeutic option to achieve LDL-C goals as recommended for He-FH and can prevent ASCVD events as reported in large clinical trials. Long-term treatment with statins and ezetimibe seems to be effective at preventing ASCVD recurrence when LDL-C is maintained below 130 and 100 mg/dL for primary and secondary prevention, respectively. Graphical abstract: Image 1 Highlights: An early diagnosis is advisable to ensure the best LLT in subjects affected by HE-FH and reduces LDL-C burden on vessels. Reaching lipid targets can reduce ASCVD risk, but if impossible, an early, lasting and lower LDL-C reduction is useful. PCSK9 inhibitors allow to reach therapeutic targets more easily, but early oral LLT may reduce the onset of ASCVD. HE-FH patients carrying LDL receptor variants without residual activity had higher ASCVD risk and need a more intense LLT.